Political Selection When Uncertainty Is High - Thushyanthan Baskaran; Zohal Hessami; Temurbek Khasanboev (Institute of Labor Economics (IZA), 2022)
Do voters place their trust in tried and tested leaders when uncertainty is high or do they prefer a new slate of leaders who are arguably more competent? To study this question, we make use of hand-collected data on 402,385 candidates who competed in open-list local council elections (1996-2020) in Bavaria. The 2020 elections took place at the dawn of the Covid-19 pandemic, a time of high uncertainty about the future course of events. Using local heterogeneity in Covid-19 outbreaks and related school/daycare closures to proxy the degree of perceived uncertainty across Bavarian municipalities, we show with a difference-in-differences design that councilors' incumbency advantage declined more in exposed municipalities. This decrease in the incumbency advantage is limited to male and non- university educated incumbents, resulting in shifted patterns of political selection. Overall, we conclude that voters select more competent politicians when they face uncertainty about the future.
Keywords: D72; D78; H70; J13; J16; 330; political selection; council elections; incumbency; Bavaria; COVID-19; uncertainty